Preliminary psychometric properties of the Common Intervention Scale (CIS): an instrument to study actions of therapists from different theoretical framework - Manubens, Rocío Tamara; Gómez Penedo, Juan Martín; Juan, Santiago; Roussos, Andrés J. (Pensando Psicología, 2019)
Objetives: This article aims to present the Scale of Common Interventions (EIC), an instrument aimed at exploring the use of psychotherapeutic interventions used by therapists of different theoretical frameworks and analyze its psychometric properties. Methodology: A non-probabilistic sample of 101 psychoanalytic and cognitive behavioral therapists completed an online version of the scale based on the last session with an adult patient. Based on this data preliminary reliability analyzes and an exploratory factor analysis was performed. Subsequently, to validate the factorial structure of the instrument, a confirmatory factor analysis was performed, based on data from a new sample of 213 therapists identified with various theoretical frameworks that completed the scale. Results: The exploratory factor analysis suggested a first solution of three factors; as one of them did not have the minimum required items per factor, said items were excluded and a new factor analysis was generated that resulted in a two-factor solution, which explained 71.1% of the total variance. The ordinal α coefficients presented levels adequate reliability in both factors. Confirmatory factor analysis showed that all estimated standardized loads of the nine items presented parameters significant (p <0.001). Discussion: The EIC is presented as a scale, which has evidence of validity and reliability, which as a short and simple instrument can represent a valuable contribution to studies aimed at evaluating psychotherapeutic interventions in the Latin American context.